Internationalization, the Curriculum and the Disciplines - de Wit, Hans; Leask, Betty (International Higher Education, 2015)
Institutions of higher education, national governments and (inter)national organizations have become more proactive, comprehensive, diverse, and innovative in their approaches to internationalization. Critical reflection on their outcomes, and in particular their impact on student learning, has resulted in a search for approaches to internationalization that have deeper meaning and greater impact. However, it is only relatively recently that questions related to the relationship between the internationalization of higher education, the curriculum and the disciplines have been explored in depth. Some of these questions are discussed, such as the relationship between ‘at home’ and ‘abroad’, the role of mobility, the role of contexts and the definition of internationalization of the curriculum.